2020
DOI: 10.1159/000510883
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of Lead Orientation in Directional Deep Brain Stimulation

Abstract: <b><i>Background:</i></b> Directional deep brain stimulation (DBS) enlarges the therapeutic window by increasing side-effect thresholds and improving clinical benefits. To determine the optimal stimulation settings and interpret clinical observations, knowledge of the lead orientation in relation to the patient’s anatomy is required. <b><i>Objective:</i></b> To determine if directional leads remain in a fixed orientation after implantation or whether orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
6
13
0
Order By: Relevance
“…We provide evidence for comparable results between GUIDE XT™ and the protocol offered in Lead-DBS. As demonstrated by two recent studies using CT and rotation fluoroscopies, deviations from the intended orientation of DBS leads occur during surgery but seem to be stable over long periods of time postoperatively [21,22]. These results support that once-only determination of the actual individual lead orientation being sufficient and that longitudinal reassessments might not be necessary.…”
Section: Discussionsupporting
confidence: 66%
“…We provide evidence for comparable results between GUIDE XT™ and the protocol offered in Lead-DBS. As demonstrated by two recent studies using CT and rotation fluoroscopies, deviations from the intended orientation of DBS leads occur during surgery but seem to be stable over long periods of time postoperatively [21,22]. These results support that once-only determination of the actual individual lead orientation being sufficient and that longitudinal reassessments might not be necessary.…”
Section: Discussionsupporting
confidence: 66%
“…60 minutes after implantation of the rst lead) was not signi cant if compared to TP1 indicating that unintended lead rotation is a very early event. This assumption is in line with the observation of other studies, which reported stable positioning for time latencies of 4-9 days or a median time latency of 82 (range 1-811) days [2,3,11].…”
Section: Discussion/ Conclusionsupporting
confidence: 92%
“…Dembek and colleagues have shown that there is no rotation over time after their first postoperative CT scan~24-72 h after implantation [13]. We carried out this investigation to evaluate the immediate time course (< 25 h) of the rotational deviation at the contact level of dDBS electrodes implanted with torsion.…”
Section: Discussionmentioning
confidence: 99%